Pembuatan Bibliografi Beranotasi Koleksi Museum Joang 1945 di Dewan Harian Daerah Badan Pembudayaan Kejuangan 45 Provinsi Sumatera Barat - Sari, Intan Permata; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractIn this paper discussed about how the creation of Annotated Bibliography Collection 1945 Joang on Library â€œDewan Harian Daerah Badan Kejuangan 45 West Sumatra province. Making this bibliography has a purpose for simplify visitors in search of information about book joang owned library â€œ Dewan Harian Daerah Badan Pembudayaan Kejuangan 45â€ West Sumatra Province. The writing of this paper uses the descriptive methods i.e. with engineering data collection through direct observation, by looking at theÂ physical state ofÂ the reference collections of book and libraries â€œDewan Harian Daerah Badan Pembudayaan Kejuangan 45â€ West Sumatra Province. As many as 172 titles become the object of research in accordance with title taken by the author about the book collection Museum Joang 1945 selected will be drawn up based on the stage of the preparation of a good bibliography format America Pshycological Assiciation (APA) with several phases.Keyword: Annoted Bibliography, Museum Joang 1945.